Epistemologi Tauhid dan Integrasi Ilmu: Telaah Pemikiran Syed Muhammad Naquib al-Attas - Irfani, Salistya; Siswanto Siswanto (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the epistemology of monotheism from the perspective of Syed Muhammad Naquib al-Attas as outlined in his book Islam and Secularism. The main focus of this study is the unity of revelation and reason, monotheism as a basic principle of science, the rejection of secular epistemology, and the ultimate goal of science, which in this context is ma'rifatullah (knowing God). This study uses a library method with a qualitative-descriptive approach and text analysis (content analysis), focusing on Chapters III and V in al-Attas's book, as well as relevant supporting literature on the epistemology of monotheism and the Islamization of science. The results show that the epistemology of monotheism according to al-Attas emphasizes the importance of integration between reason, revelation, and spiritual experience. In this view, science is not only intellectual, but also moral and spiritual. This integration forms a holistic framework of science, which not only functions to develop human morals and character, but also as a means to know and serve God. Thus, the epistemology of monotheism provides a strong foundation for the development of Islamic science, while strengthening the identity of Islamic science in facing the challenges of modernity.